Maintenance and assessment of cell viability in formulation of non‐sporulating bacterial inoculants. Issue 2 (4th December 2017) - Berninger, Teresa; González López, Óscar; Bejarano, Ana; Preininger, Claudia; Sessitsch, Angela
Summary: The application of beneficial, plant‐associated microorganisms is a sustainable approach to improving crop performance in agriculture. However, microbial inoculants are often susceptible to prolonged periods of storage and deleterious environmental factors, which negatively impact their viability and ultimately limit efficacy in the field. This particularly concerns non‐sporulating bacteria. To overcome this challenge, the availability of protective formulations is crucial. Numerous parameters influence the viability of microbial cells, with drying procedures generally being among the most critical ones. Thus, technological advances to attenuate the desiccation stress imposed on living cells are key to successful formulation development. In this review, we discuss the core aspects important to consider when aiming at high cell viability of non‐sporulating bacteria to be applied as microbial inoculants in agriculture. We elaborate the suitability of commonly applied drying methods (freeze‐drying, vacuum‐drying, spray‐drying, fluidized bed‐drying, air‐drying) and potential measures to prevent cell damage from desiccation (externally applied protectants, stress pre‐conditioning, triggering of exopolysaccharide secretion, 'helper' strains). Furthermore, we point out methods for assessing bacterial viability, such as colony counting, spectrophotometry, microcalorimetry, flow cytometry and viability qPCR. Choosing appropriate technologies for maintenance of cell viability and evaluation thereof will render formulation development more efficient. This in turn will aid in utilizing the vast potential of promising, plant beneficial bacteria as sustainable alternatives to standard agrochemicals. Abstract : Biostimulants and biopesticides based on non‐sporulating bacteria are of great interest in agriculture, but their low shelf life and efficacy under field conditions is often a limiting factor to practical application. Protective formulations are thus necessary. A range of methods to maintain and monitor cell viability is presented to decide on suitable approaches for formulation development.